The Rock Sdn. Bhd / Nur Syafiqah Farhanah Mohd Hilmi ... [et al.] - Mohd Hilmi, Nur Syafiqah Farhanah; Noordin, Norasyiqin Mohd; Harizam, Wafiy Aida; Ariffin, Nadhirah Shamsul; Mohd Ali, Nur Nabilah Husna (2017)
After conducting initial study towards available shoe rack design on market, the team had chosen a product that can give advantage to individual and household. Our product is called Rock. Rock has the abilities to store, wash, dry, and groom your shoes. Nowadays, individual yet family are very busy with their works and social life; ergo they did not have much time to manage or take care of their shoes. Especially when it comes to a person demands extra shoe care. This product is suitable for career's person or a family who has children.